A Critique on prosecutorial independence in Kenya: the Office of the Director of Public Prosecutions and its effects on the attainment of the rule of law - Dido, Diana Madina (Strathmore University, 2018)
A Critique on prosecutorial independence in Kenya: the Office of the Director of Public Prosecutions and its effects on the attainment of the rule of law Prosecution is a key role within the criminal justice system. In Kenya the Office of the Director of Public Prosecutions (ODPP) is responsible for prosecution. The ODPP being a relatively new institution that is critical within the criminal justice system, makes it important to gauge its progress early enough to ensure it operates optimally. Therefore, the main aim of this paper is to analyze the effects of prosecutorial independence to the ODPP's role in the attainment of the rule of law. The study gives a critical analysis of the development of prosecutorial independence. in Kenya. It goes further to analyze the effects of this independence to the functions of the ODPP in a bid to assess the consequent impact on the attainment of the rule of law. The study is undertaken through a comprehensive data analysis of cases and reports. The study hence finds that prosecutorial independence has facilitated the attainment of the rule of law through the ODPP's mandate. The study further goes ahead and gives recommendations aimed at improving the ODPP's operations consequently facilitating the attainment of the rule of law.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Prosecutorial independence - Kenya; Office of the Director of Public Prosecutions (ODPP); Rule of law